Pirate Traces - Gabriela Méndez Cota (Media Theory, 2020)
Late in the summer of 2019, Gary Hall gave a series of talks hosted by the Philosophy Department at Universidad Iberoamericana, Mexico City. One of them was titled ‘Liberalism Must be Defeated. On the Obsolescence of Bourgeois Theory in the Anthropocene’. As the organizer of this event, I was curious about the reception of this argument in a context that does not usually name ‘liberalism’ as the enemy, even though it is no stranger to anti-bourgeois positions on intellectual activity. Universidad Iberoamericana is a private Jesuit college that has catered historically to the Mexican elites while upholding a reputation for its political commitments to democracy and social justice. Indeed, one could argue that it is a liberal alliance between religion and business that provides the conditions for the Philosophy Department’s younger generation of scholars to teach and write about the kind of (French, German, Italian) radical theory that Gary Hall’s work embraces and seeks to renew. While most attendants of the talk at IBERO did not at all lack the theoretical framework to understand in what sense liberalism must be defeated, or why bourgeois theory should be regarded as obsolete, I was curious about the conditions of taking Hall’s performative argument on board. Was it a critique of how successful Anglo scholars operate, or was it also about how ‘we’ operate here in Mexico City? Is ‘our’ work liberal bourgeois theory too, and therefore obsolete? If so, could we do better than appear tolerant of a disruptive performance that was challenging us to aspire to something different, something unknown, something like existing otherwise?